Die materielle Selektivität steuerlicher Beihilfen - Ellenrieder, Benedikt (Mohr Siebeck, 2020)
Since the late nineties, fiscal aid measures have become massively important in both theory and practice, partly because of the high-profile interest created by some drastic legal consequences. Benedikt Ellenrieders in-depth analysis is devoted to the selectivity criterion, which usually determines the aid status of tax measures.
PublicationDate: 20201218
Keywords: Raum -- Steuerverfassungsrecht -- Europäisches Steuerrecht -- Internetdiensteanbieter -- privatrechtliches Unrecht -- Internationales Steuerrecht -- Beihilfe -- Menschenrechtsverletzung -- Verwaltungsrecht -- Besonderes Verwaltungsrecht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Europarecht